Direct plasma synthesis of nano-capsules loaded with antibiotics. Issue 11 (20th February 2017) - Lo Porto, C.; Palumbo, F.; Palazzo, G.; Favia, P.
Abstract : Vancomycin containing nano-capsules have been synthesized in one step by means of aerosol-assisted atmospheric pressure plasma. Abstract : We report the first observation of a plasma assisted, one-step deposition of nanometric capsules. The deposited spherical structures contain vancomycin and can be prepared by means of an aerosol-assisted atmospheric pressure Dielectric Barrier Discharge (DBD) reactor. The core–shell structure of the nano-capsules is clearly attested by scanning electron and confocal microscopy.